Forecasting direct investment equity income for the Danish balance of payments - Jannick Damgaard; Mathies Lau Friis Hansen; Robert Wederkinck (Danmarks Nationalbank, 2010)
Late and significant revisions are often observed in direct investment equity income, hampering the quality of preliminary balance of payments statistics. We test a range of models and find that forecasts for direct investment equity income based on a combination of past profitability and consensus data for changes in expected private consumption growth outperform the current forecasts solely based on historical profitability. When the refined models are applied to the Danish balance of payments, the largest improvements are observed for outward and inward direct investment separately. Revisions on net direct investment equity income only decrease marginally because the significant revisions in gross terms resulting from the historical models have a tendency to (partly) cancel out each other on a net basis.
Keywords: 330; Prognoseverfahren; Zahlungsbilanz; Direktinvestition; Zahlungsbilanzstatistik; Dänemark